Predictive Factors of Patient Satisfaction with Pharmacy Services in South Korea: A Cross-Sectional Study of National Level Data - Lee, Sunkyung (PLoS One, 2015)
OBJECTIVES: Patient satisfaction has emerged as a prerequisite to improving patients’ health behaviors leading to better health care outcomes. This study was to identify predictive determinants for patient satisfaction with pharmacy services using national-level data. METHODS: A cross-sectional evaluation was conducted using 2008 Korean National Health and Nutrition Examination Survey (KNHANES) data. To assess the predictive factors for patient satisfaction with pharmacy services, an ordinal logistic regression model was conducted adjusting for patient characteristics, clinical comorbidities, and perception of health. RESULTS: A total of 9,744 people, a representative sample of 48.2 million Koreans, participated in the 2008 KNHANES, of whom 2,188 (23.6%) reported visits to pharmacy within the last 2 weeks prior to the survey. Of the patients who visited the pharmacy, 74.6% reported to be either “very satisfied” or “satisfied,” and 25.4% responded as being “neutral,” “dissatisfied,” or “very dissatisfied.” A multivariate ordinal logistic regression analysis with weighted observations revealed that patients with fair perception of health (adjusted OR 1.32; 95% CI 1.01–1.74; p<0.05) and those with middle to low family incomes (adjusted OR 1.34; 95% CI 1.02–1.76; p<0.05) were more likely to be satisfied with pharmacy services, and employment-based insurers were less likely to be satisfied with pharmacy services (adjusted OR 0.80; 95% CI 0.65–0.97; p<0.05). CONCLUSION: Our findings indicated that three out of four patients expressed satisfaction toward pharmacy services. Middle to low family incomes, fair perception of health, and employee insured individuals were significant predictors of patient satisfaction with pharmacy services.